As the twig is bent, so is the tree inclined: Lack of prior knowledge as a driver of academic procrastination. (10th December 2021) - Fulano, Celso; Magalhães, Paula; Núñez, José C.; Marcuzzo, Simone; Rosário, Pedro
ABSTRACT: Academic procrastination can be described as the delayed completion of academic tasks. This behavior is pervasive among students from different grade levels and cultures. A structural equation model was run to analyze the relationships between prior knowledge and procrastination in mathematics mediated by self-regulated learning and self-efficacy in mathematics. The model was analyzed using a sample of 1, 000 Mozambican students from the 10th and 12th grades. Results indicated that both self-regulated learning and self-efficacy in mathematics were positively explained by prior knowledge in mathematics. Moreover, self-efficacy in mathematics was found to be positively related to self-regulated learning, and both were negatively related to mathematics procrastination. Finally, self-regulated learning and self-efficacy in mathematics mediated the effect of prior mathematics knowledge on mathematics procrastination. The study discusses these findings as well as their consequences, possible educational implications, and suggestions for educational practice.